Grand Hotel Abyss: The Lives of the Frankfurt School: by Stuart Jeffries. London: Verso, 2016. Issue 4 (2nd October 2019) - Black, Jack
Abstract : This review considers Stuart Jeffries's Grand Hotel Abyss: The Lives of the Frankfurt School . Providing a detailed account of the work and lives of the Frankfurt School, Jeffries is commended for his ability to present an illustrative biography of the school's members and associates as well as the variety of topics that their work engaged with. However, while Jefferies manages to merge biography and academic theory in a readable and at times detailed and engaging narrative, such work is undermined by a tendency to focus on the salacious gossip of a group of men whose real-life complications tend to overcome the significance of their arguments. Nevertheless, in view of the Frankfurt School's work, it is suggested that the book's paradoxes can serve as an important opening to contemporary topics and, more importantly, to theorizing these contradictions in light of the Frankfurt School.